Inhibiting miR-22 Alleviates Cardiac Dysfunction by Regulating Sirt1 in Septic Cardiomyopathy - Wang, Runze; Xu, Yuerong; Zhang, Wei; Fang, Yexian; Yang, Tiqun; Zeng, Di; Wei, Ting; Liu, Jing; Zhou, Haijia; Li, Yan; Huang, Zhan-peng; Zhang, Mingming (Frontiers in Cell and Developmental Biology, 2021)
High morbidity and mortality are the most typical characteristics of septic cardiomyopathy. We aimed to reveal the role of miR-22 in septic cardiomyopathy and to explore the underlying mechanisms. miR-22 cardiac-specific knockout (miR-22cKO) mice and miR-22 cardiac-specific transgenic (miR-22cOE) mice were subjected to a cecal ligation and puncture (CLP) operation, while a sham operation was used in the control group. The echocardiogram results suggested that miR-22cKO CLP mice cardiac dysfunction was alleviated. The serum LDH and CK-MB were reduced in the miR-22cKO CLP mice. As expected, there was reduced apoptosis, increased autophagy and alleviated mitochondrial dysfunction in the miR-22cKO CLP mice, while it had contrary role in the miR-22cOE group. Inhibiting miR-22 promoted autophagy by increasing the LC3II/GAPDH ratio and decreasing the p62 level. Additionally, culturing primary cardiomyocytes with lipopolysaccharide (LPS) simulated sepsis-induced cardiomyopathy in vitro. Inhibiting miR-22 promoted autophagic flux confirmed by an increased LC3II/GAPDH ratio and reduced p62 protein level under bafilomycin A1 conditions. Knocking out miR-22 may exert a cardioprotective effect on sepsis by increasing autophagy and decreasing apoptosis via sirt1. Our results revealed that targeting miR-22 may become a new strategy for septic cardiomyopathy treatment.